Constitutional guarantees of human rights in civil proceedings, the Republic of Kazakhstan. (Journal of actual problems of jurisprudence, 2016)
This article discusses the features of the constitutional guarantees of human rights in civil proceedings in the Republic of Kazakhstan. The influence of the principle of separation of powers in the exercise of civil proceedings.
Keywords: human rights; constitutional guarantees of social and economic guarantees